Job Burnout and Organizational Cynicism Among Employees in Nigerian Banks - Akhigbe, Omoankhanlen Joseph; Gail, Oyam-Jajaboma (European Scientific Journal, ESJ, 2017)
Job burnout and organizational cynicism are two intertwined phenomena which have adverse effects on organizations. The main purpose of this study is to examine the relationship between job burnout and organizational cynicism of employees in Nigerian Banks. The study adopted the cross-sectional survey method which is a form of the quasi-experimental research design. The study had a sample size of 214 employees drawn out from an accessible population of 499 bank employees in Port Harcourt using the Krejcie& Morgan (1970) table. The study research instruments were distributed to the accessible population using the Bowley’s (1964) population allocation formula of proportion. The Spearman rank correlation coefficient was used in testing the study hypotheses. The study findings reveal that there is a significant relationship between the two dimensions of job burnout used in this study and organizational cynicism. The study recommended among others that banks should give their employees breaks and time off from time to time in order to guide against emotional exhaustion since it has a significant relationship with organizational cynicism, this would give employees the opportunity to balance their work-life and family life. Conclusively, the study has extensively looked at the relationship between job burnout and organizational cynicism.